Management of financial institutions on the basis of corporate social responsibility as a driver of sustainable development - Khovrak, Inna; Polinkevych, Oksana; Trynchuk, Viktor (<center>Conference Proceedings Determinants Of Regional Development</center>, 2021)
The article explores issues of ensuring sustainable development by implementing the social responsibility concept in the financial institutions’ management system. The research methodology is based on a literature review, expert survey, qualitative case study. The obtained results allow to improve the strategic tools for strengthening corporate social responsibility of financial institutions in the process of ensuring sustainable development, to justify the need to manage the reputation of financial institutions, and to propose an approach to the formation of management decisions taking into account the values and norms of corporate social responsibility.